En kontinuerlig, høyoppløselig rekonstruksjon av brefluktuasjoner på Hambergbreen, Syd Georgia, de siste 1500 år - Vatle, Sunniva Solheim (The University of Bergen, 2012)
A sediment record from a distal-glacial fed lake has the potential to contain continuous, high-resolution record of glacial fluctuations backwards in time. In this thesis multiple sediment cores from Middle Hamberg Lake, at South Georgia, Southern Ocean, has been used to reconstruct glacial fluctuations on the Hamberg Glacier at high temporal resolution. The multi proxy analyses on the sediments from the distal glacier-fed lake show that the Hamberg Glacier has been very dynamic over the last 1500 years. During the time period AD 400-730, the Hamberg Glacier was in an advanced position followed by a rapid retreat up until AD 770, when it halted approximately at the same position as the present day glacier. During the following centuries the glacier gradually increased until AD 1300 and thereafter retreated until 1470 when the glacier advances associated with the Little Ice Age (LIA) began. During the LIA, the glacier had its maximum advance twice; close to AD 1600 and AD1800. The glacier halted in an advance position covering the Upper Hamberg Lake until the end of 1990s. Over the most recent 30 year period, by contrast, the Hamberg Glacier has receded rapidly to its present minimum. The increasing air temperatures and sea surface temperatures in Antarctica is interpreted as the main contributor for the retreat of the glacier The reconstructed glacial fluctuations on the Hamberg Glacier have further been compared with reconstructed glacial fluctuations at Austre Okstindbre, Northern Norway, and the pattern variability are clearly out of phase and also in periods in anti-phase. This anti-phasing pattern of glacier variability may be caused by the bi-polar seesaw effect that also is seen in modern day instrumental data. Master i Geovitenskap MAMN-GEOV GEOV399